2021
DOI: 10.1002/pd.5957
|View full text |Cite
|
Sign up to set email alerts
|

Overview and recent developments in cell‐based noninvasive prenatal testing

Abstract: Investigators have long been interested in the natural phenomenon of fetal and placental cell trafficking into the maternal circulation. The scarcity of these circulating cells makes their detection and isolation technically challenging. However, as a DNA source of fetal origin not mixed with maternal DNA, they have the potential of considerable benefit over circulating cell‐free DNA‐based noninvasive prenatal genetic testing (NIPT). Endocervical trophoblasts, which are less rare but more challenging to recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 133 publications
(271 reference statements)
1
45
0
Order By: Relevance
“…Numerous studies have shown that NIPT‐plus detects common fetal chromosome aneuploidies with high sensitivity and specificity compared with conventional methods (Kim et al, 2021; Merriel et al, 2021; Vossaert et al, 2021). While it varied widely in different centers, the PPV range of T21 was 79%–94%, of T18 was 54vs.–85%, and of T13 was 13vs.–62% (Deng et al, 2021; Hu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that NIPT‐plus detects common fetal chromosome aneuploidies with high sensitivity and specificity compared with conventional methods (Kim et al, 2021; Merriel et al, 2021; Vossaert et al, 2021). While it varied widely in different centers, the PPV range of T21 was 79%–94%, of T18 was 54vs.–85%, and of T13 was 13vs.–62% (Deng et al, 2021; Hu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Initial attempts focused on intact circulating fetal nucleated red blood cells as well as trophoblasts, with variable success. 2,6 Ever since the discovery in 2008 that maternal plasma contains fragmented cell-free DNA (cfDNA) of which a proportion is of fetal origin, 7 cfDNA-based screening of pregnant women for the presence of fetal aneuploidy, copy number variants, and more recently for selected single gene disorders, has been developed and integrated into clinical prenatal care. [8][9][10][11] Currently, cell-free NIPT (cfNIPT) is widely used for screening purposes for common fetal aneuploidies such as trisomy 21, 18, and 13, but it has limitations, including a lower positive predictive value for rarer conditions and sub-chromosomal copy number variants, and a poorer performance in certain circumstances, for example, for women with a higher body mass index (BMI).…”
Section: Introductionmentioning
confidence: 99%
“…9,13 As it is currently not possible to specifically purify the fetal cfDNA, we and others have continued to develop and refine assays for isolation and analysis of intact fetal cells from the maternal blood circulation or via endocervical sampling, as an alternative DNA source of fetal origin. 2,3,14 Prior research to which we contributed focused on the analysis of circulating trophoblasts (TBs) isolated from maternal blood and demonstrated accurate detection of fetal aneuploidy and copy number variants greater than 1 Mb in size when cells are successfully isolated. 3,15 In a validation study of 95 samples, circulating TB cells were recovered from 97.9% of pregnant women and were used to diagnose selected aneuploidies and copy number variants.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations